South Stream Project and the Ukrainian Factor - Roxana Ioana Banciu (Romanian Journal of European Affairs)
The paper seeks to develop an analysis of the South Stream project in view of the Ukrainian crisis. We cannot put aside the internal factor as Ukraine is facing serious internal issues such as corruption and instability, therefore Russia’s invasion of Ukraine can not be simply ignored in this pipeline project. The article uses mostly facts that happened throughout last years, as well as for and against declarations in the case of the South Stream project and its mother Russia. When we hear about South Stream, we think of Russia and since 2007, this pipeline has encouraged Putin’s faith in energy superpower. A good point to start with was to gather all declarations since then and cover all actions that regard the South Stream game. In Russian foreign policy for the South Stream race, Soft Power was used more than enough and it has recently made room for Hard Power, which is the Ukraine never ending episode. Insights of the South Stream story have been lately related both softly and hardly, this is the reason why I have chosen to analyse both sides in order to complete the energy landscape.